Experimental and theoretical study of AC losses in variable asymmetrical magnetic environments. (6th July 2017) - Ranecky, S T; Watanabe, H; Ogawa, J; Oka, T; Gölden, D; Alff, L; Genenko, Y A
Abstract: Measurements of AC losses in a HTS-tape placed in between two bulk magnetic shields of high permeability were performed by applying calorimetric techniques for various asymmetrical shielding arrangements. The experiment was supported by analytical calculations and finite-element simulations of the field and current distributions, based on the Bean model of the critical state. The simulated current and field profiles perfectly reproduce the analytic solutions known for certain shielding geometries. The evaluation of the consequent AC losses exhibits good agreement with measurements for the central position of the tape between the magnets but have increasing discrepancy when the tape is approaching the shields. This can be explained by the increasing contribution of the eddy currents and magnetic hysteresis losses in the conducting shields.